2020
DOI: 10.1002/smll.201904756
|View full text |Cite
|
Sign up to set email alerts
|

Precontrolled Alignment of Graphite Nanoplatelets in Polymeric Composites Prevents Bacterial Attachment

Abstract: Graphene coatings composed of vertical spikes are shown to mitigate bacterial attachment. Such coatings present hydrophobic edges of graphene, which penetrate the lipid bilayers causing physical disruption of bacterial cells. However, manufacturing of such surfaces on a scale required for antibacterial applications is currently not feasible. This study explores whether graphite can be used as a cheaper alternative to graphene coatings. To examine this, composites of graphite nanoplatelets (GNP) and low‐density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 38 publications
(61 reference statements)
1
31
0
Order By: Relevance
“…Previous studies by authors revealed also other interesting physical properties that these nanocomposites with aligned GNPs exhibit as: gas barrier properties, [79,80] enhanced mechanical performance, [81] or anisotropic electrical and thermal conductivity [78,81] . A schematic of the manufacturing process is shown on Figure 6, with more details found in our previous study [54] . Moreover, the experimental trials have included two types of LDPE, differing in viscosity by around one order of magnitude.…”
Section: Graphene‐based Antimicrobial Surfacesmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies by authors revealed also other interesting physical properties that these nanocomposites with aligned GNPs exhibit as: gas barrier properties, [79,80] enhanced mechanical performance, [81] or anisotropic electrical and thermal conductivity [78,81] . A schematic of the manufacturing process is shown on Figure 6, with more details found in our previous study [54] . Moreover, the experimental trials have included two types of LDPE, differing in viscosity by around one order of magnitude.…”
Section: Graphene‐based Antimicrobial Surfacesmentioning
confidence: 99%
“…Graphene and graphene derivatives can be attached to other surfaces as coatings for example by electrical and chemical deposition methods, [14–16,38–40] layer‐by‐layer assembly [41,42] or various surface spreading methods [43–48] . Finally, gel spinning, [49] electrospinning, [50,51] layer‐by‐layer assembly [41,52,53] or melt extrusion [54] have been used to create graphene based antibacterial nanocomposites. The method of obtaining the antibacterial surfaces is essential as it dictates the extent to which such surfaces can be tuned in terms of orientation and distribution of the graphene and their upscaling potential.…”
Section: Graphene‐based Antimicrobial Surfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last 15 years, the performance of high aspect ratio fillers has shown great promise and opened a wide range of opportunities in the area of polymer nanocomposites [ 1 ]. Consequently the use of different fillers of high-aspect ratio has led to the development of high-performance and multifunctional materials with a wide range of industrial applications, for example, as gas-barrier membranes [ 2 , 3 , 4 , 5 ], antibacterial surfaces [ 6 , 7 , 8 ], heat-sinks [ 9 , 10 ] and electronics [ 11 ].…”
Section: Introductionmentioning
confidence: 99%